Impacts of Regeneration Failure in Population Structire Indan Sandalwood Forest in Marayoor, Kerala - M V, Durai (Indian Forester, 2023)
Sandalwood (Santalum album) is one of highly prized timber species in the world for its fragrance. The success of its regeneration in forest is highly dependent on seed production, seed dispersal, germination, vitality of a species and presence of biotic disturbances. The present study was conducted in different naturalized sandalwood reserves (SRs) in Marayoor, Kerala to understand population structure and natural regeneration status of sandalwood.Â  All SRs are having un-balanced population structure and seedlings (<30cm girth at breast height) account <4% of the total stems, which indicates indicate a declining population. Regeneration of sandalwood could not improve in all SRs due to heavy grazing by wild animals and cattle despite artificial regeneration and abundant of seed production.Â 